Consumer Behaviour In Halal Food: A Systematic Mapping Study - Anita Maulina; Nur Fitri Rahmawati; Anisa Arizona (Yayasan Ilomata, 2020)
This article discusses Consumer Behaviour in Halal Food using a Systematic Mapping Study. The purpose of this mapping study is to find out what topics about Halal food have been researched by scientists around the world. The search was conducted through the research article databases such as Emerald, ScienceDirect, ProQuest, and Taylor & Francis Online. Searches were only carried out on articles published between 2015 - 2020. The inclusion criteria were articles from scientific journals only. The results of this mapping study can be used as a reference for finding new topics in research on Halal Food.